2018
DOI: 10.1002/lio2.166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of absorbable PLA nasal implants in an ovine model

Abstract: ObjectiveTo examine biocompatibility and absorption profile of a poly (L‐lactide‐co‐D,L‐lactide) 70:30 nasal implant.MethodsIn an ovine model, 66 rod‐shaped absorbable implants were placed in 11 nasal dorsa. The sheep were sacrificed at 1.5 (N = 3), 6 (N = 3), 12 (N = 3), 18 (N = 1), and 24 months (N = 1). The nasal dorsum was harvested from each animal. Gross and histopathological examinations were performed.ResultsThere were no postoperative complications, signs of infection, or tissue rejection throughout f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The outcomes at 24 months should be representative of long-term improvement since the implant is absorbed by the body over a period of approximately 18 months. 13,14 The lack of a control group is the limitation of this study. Although these were single-arm studies comparing pretreatment with post-treatment outcomes within patient, a recent randomized control trial has demonstrated the superiority of the implant over a sham procedure for the treatment of NVC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The outcomes at 24 months should be representative of long-term improvement since the implant is absorbed by the body over a period of approximately 18 months. 13,14 The lack of a control group is the limitation of this study. Although these were single-arm studies comparing pretreatment with post-treatment outcomes within patient, a recent randomized control trial has demonstrated the superiority of the implant over a sham procedure for the treatment of NVC.…”
Section: Discussionmentioning
confidence: 94%
“…The outcomes at 24 months should be representative of long-term improvement since the implant is absorbed by the body over a period of approximately 18 months. 13 14…”
Section: Discussionmentioning
confidence: 99%
“…Follow‐up for this study was limited to 12 months postprocedure. Previously, animal histology studies have shown that an implant of the same composition is absorbed over 18 to 24 months after implantation and that, upon complete absorption, the implant is replaced with nodular bundles of mature collagenized fibrous tissue that may provide mechanical strength at the lateral wall . Therefore, additional follow‐up out to 24 months would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a bioabsorbable implant (Latera, Spirox Inc., Redwood City, CA) comprised of 70:30 copolymer of poly(l‐lactide) and poly(d‐lactide), which can be placed under local anesthesia in the physician's office or under general anesthesia in the operating room (OR), was used to address dynamic NVC by supporting the nasal lateral wall . Animal studies showed that the implant material was biocompatible and was absorbed over 18 to 24 months postoperatively . Combined interim 6‐month safety and effectiveness results of two studies using this bioabsorbable implant have been reported in a mix of patients who received the implant in an OR or office setting .…”
Section: Introductionmentioning
confidence: 99%
“…From an animal study, the implant material had structural degradation and active absorption at 18 months postimplantation. 21 Once completed absorbed around 24 months, the implant was replaced by mature collagenized fibrous tissue. 21 From these results, the authors hypothesize that the fibrocollagenous scar tissue may provide support to the lateral wall over time, resulting in a prolonged improvement that outlasts the mechanical integrity of the absorbable implant.…”
Section: Discussionmentioning
confidence: 99%